Research on spatial characteristics and planning patterns of settlements in the Jingjiang River Flood Diversion Area, China - Zhou, Yan; Jiang, Hong; Lu, Tianyang (International Planning History Society Proceedings, 2024)
In the context of the shortage of land resources in China, there are some human settlements built in the flood diversion areas. These settlements are planned and constructed in conjunction with water conservancy projects arranged by the state, and assume the function of resettlement and flood control. Taking Jingjiang River Flood Diversion Area, an important large-scale water conservancy project constructed in China's Changjiang River Basin in the 1950s, as the research area, this study aims to reveal the planning pattern of the settlement spaces built in this special area in the early period of New China. In this article, the development of its hydraulic environment and human settlements is sorted out. Based on this, the location, scale, form and layout of the 19 refuge areas are analysed, and their formation logic is explored. The results show that the refuge areas in the Jingjiang River Flood Diversion Area have developed unique spatial characteristics driven by flood diversion, resettlement and agricultural production needs. Their physical space is closely related to the water conservancy facilities, developing a specific pattern highly adapted to flood diversion, which has the effect of improving the security of residents' life and production, and reflects the planning ideas of "coexisting with the water and integrating as a whole". The research findings contribute to the recognition of the value characteristics of settlements in flood diversion areas, and provide a reference for the understanding of the national governance during the early period of New China.